The importance of tourist facilities in developing domestic tourism: Karbala as a model - Adel Fadhil Jawad (Peerian Journals Publishing, 2025)
This study aims to clarify the current state of tourism facilities in the city of Karbala and their impact on tourism activity. The research addresses a central problem involving several questions revolving around the weakness of the tourism industry and the potential for its development in certain economies. Notably, tourism activity in the study area (the holy city of Karbala) has witnessed gradual growth following the improvement in security conditions. It is important to note that investment in tourism is one of the fastest means to achieve the desired goals of development plans. To achieve the objective of the study, the researcher employed an analytical and evaluative methodology by comparing tourism facilities and the number of tourists in Karbala relative to Iraq as a whole, using a scientific approach. The current study reached several significant scientific and practical findings: Karbala has experienced substantial expansion in hotel infrastructure, visitor cities, and service facilities over the past two decades. This expansion has led to a remarkable increase in tourist numbers—from 2 million to over 21 million.
Keywords: Tourism Facilities; Domestic Tourism